Beyond Flexibility — Workflows in the perioperative Sector of the Healthcare Domain - Bandt, Markus; Kühn, Robert; Schick, Sebastian; Meyer, Holger (Electronic Communications of the EASST, 2011)
The OR environment of a hospital demands high standards of both qualitativeand economic management. Since the basic perioperative processes are ratherwell defined, the use of WfMS to support the planning and coordination of surgicaltreatment can be beneficial. The analysis of the perioperative work showed theneed of flexibility at certain points in the processes. Within the project PERIKLESa corresponding YAWL model was implemented using several workflow flexibilityconcepts. A major challenge in this context was the handling of unpredictableexceptions (e.g. changing requirements during surgery). The use of exception handling is one reliable way to meet this requirements.